Analysis of Legal Confiscation of Corruption Assets from the Perspective of Justice and State Financial Recovery: Analisis Hukum Penyitaan Aset Korupsi dalam Perspektif Keadilan dan Pemulihan Keuangan Negara - Wedha, Yogi Yasa; Wijaya, Made Hendra; Apriliani, Kadek (LITIGASI, 2025)
Asset confiscation as an effort to recover state financial losses due to corruption crimes in Indonesia still faces substantial challenges. The legal framework stipulated in the Criminal Procedure Code limits confiscation only for evidentiary purposes in the judicial process, these restrictions impact the non-optimal recovery of state financial losses. This research aims to analyze the regulatory and technical substance obstacles in the implementation of asset confiscation and develop a progressive legal strategy based on the theory of justice. This research is normative juridical research that integrates John Rawls' theory of justice, Richard A. Posner's Economic Analysis of Law Theory, and Lawrence Friedman's legal system theory and the theory of legal expediency as an analytical knife as a consideration to provide recommendations for reform of special confiscation arrangements for corruption crimes. The results show that the gap between the Criminal Procedure Code and the Corruption Eradication Law worsens the effectiveness of asset confiscation, especially at the investigation stage. The expansion of objects that can be seized and the Non-conviction based (NCB) asset forfeiture approach are identified as potential solutions that are more efficient and fair in overcoming this obstacle. The proposed strategy includes expanding the scope of confiscation and harmonizing regulations between KUHAP and the Law on the Eradication of Corruption. This research confirms the importance of legal reform to improve the efficiency of recovering state losses due to corruption while strengthening a fair and beneficial legal system. The strategy of expanding asset confiscation arrangements has urgency in efforts to recover....